The species composition cyanobacteria in the cultivated soils of Dak Lak and Dak Nong provinces - Hanh, Ho Sy (Academia Journal of Biology, 2012)
A total of 129 species and subspecies of cyanobacteria were found in the cultivating soils (rice, cotton and coffee) of Dak Lak and Dak Nong provinces. They belonged to 20 genera, 10 families, 4 orders. The Ocillatoriales order was the most diverse with 71 species and subspecies (55.03% total found species); the Nostocales order with 44 species and subspecies (55.03%); Chroococcales order: 7 species (5.43%); and Stigonematales order: 7 species (5.43%). They are morphologically diverse: fibrifrom with 122 species (94.57%); unicellular with 7 species (5.43%). Among them there are 5 genera, 11 species and subspecies exicting in 3 types of cultivated soils the genera are: Lyngbya, Microcoleus, Phormidium, Nostoc and Hapalosiphon; the species are Gloeocapsa montana, Lyngbya aerugineo-coerulea, Oscillatoria brevis, Phormidium corium, Phormidium tenue, Cylindrospermum licheniforme, Nostoc carneum, Nostoc linckia, Calothrix elenkinii, Hapalosiphon welwitschi, Hapalosiphon sp. Among them 1 genus (Westiellopsis Janet), 38 species and subspecies were firstly recorded in Vietnam. Of the cultivated soils of Daklak and Daknong provinces, the rice soil was determined to possess the most species of cyanobacteria (101 species and subspecies, 18 genera, 9 families, 4 orders), it was folowed by the cotton-paddy soil (55 species and subspecies, 14 genera, 8 families, 4 orders) and the coffee-planted soil showed the least (26 species and subspecies, 11 genus, 8 families, 4 orders).